2004
DOI: 10.1021/jp048178l
|View full text |Cite
|
Sign up to set email alerts
|

IR-Luminescent PbS−Polystyrene Nanocomposites Prepared from Random Ionomers in Solution

Abstract: Hybrid composites of PbS nanoparticles embedded in sulfonated polystyrene matrixes were prepared without other added capping agent in the random ionomer. The nanocomposites were found to exhibit photoluminescence in both the near-infrared and visible regions. The infrared luminescence was tunable in the range 1100-1500 nm via quantum size effect. XRD, TEM, UV-vis, FTIR, DSC, and XPS techniques were employed to investigate the size, shape, morphology, absorption, and thermal properties as well as the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 35 publications
1
27
1
Order By: Relevance
“…3c). The main peaks ranging from 136 eV to 141.5 eV consist of the 138.5 eV (Pb 2 þ ions in perovskite structure) and 139.9 eV (Pb 2 þ ions coordinated to ÀSO À 3 groups), respectively [29,30]. As increasing the PSSH ratio in M-PEDOT:PSS, the ratio of Pb (SO3) to Pb (perovskite) (Pb (SO3) /Pb (perovskite) ) increased from 0.09 to 0.70.…”
Section: Resultsmentioning
confidence: 99%
“…3c). The main peaks ranging from 136 eV to 141.5 eV consist of the 138.5 eV (Pb 2 þ ions in perovskite structure) and 139.9 eV (Pb 2 þ ions coordinated to ÀSO À 3 groups), respectively [29,30]. As increasing the PSSH ratio in M-PEDOT:PSS, the ratio of Pb (SO3) to Pb (perovskite) (Pb (SO3) /Pb (perovskite) ) increased from 0.09 to 0.70.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, it is relatively easy to prepare particles of ∼18 nm size and it could be expected that these PbS nanoparticles will exhibit a strong quantum confinement effect. It was reported that the band gap of PbS can be widened to the visible region by forming nanoparticles [2][3][4][5][6]. PbS nanoparticles are hence promising materials in electroluminescent devices such as light-emitting diodes and luminescent display devices.…”
Section: Introductionmentioning
confidence: 99%
“…PbS nanoparticles are hence promising materials in electroluminescent devices such as light-emitting diodes and luminescent display devices. PbS nanostructures with different morphologies have been prepared including particles [3][4][5], wires [7], rods [6,8], tubes [9], and hollow spheres [10] by different methods such as wet chemistry [4,6,7], solvothermal [11], thermal decomposition [12], microwave irradiation [5], electrodeposition [13], sonochemical [5,9,10], and photochemical using UV-or γ-irradiation [3,14].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Moreover, they hold the longterm stability and will offer new routes to influencing the interactions that may take place between the matrix and the nanoparticle. 4,5 The clever combination of different nanoscale materials can lead to the development of multifunctional nanomaterials.…”
Section: Introductionmentioning
confidence: 99%